Search and inflation: a survey of the recent literature - Bonomo, Marco (Estudios de Economía, 2016)
In order to understand the macroeconomic effects of inflation, it is necessary to investigate the underlying microeconomic aspects. Inflation affects microeconomic interaction between firms and consumers in a substantial ways. Firms choose pricing rules that affect consumers’ search. The search is realized across firms and through time. The Theory does not provide a clear answer to the effect of inflation on welfare. On one hand, because of adjustment costs. A higher inflation is associated with a higher dispersion of prices, making search more attractive. On the other hand, inflation deteriorates the information content of prices, reducing the ability of consumers to take advantage of the dispersion of prices through search. This article surveys very recent contributions to this subject. It argues that although on can get important insights from this literature, it does not provide a satisfactory answer to the question that has puzzled macroeconomists for more than two decades: how to explain the social costs of inflation?